2020
DOI: 10.1111/cga.12403
|View full text |Cite
|
Sign up to set email alerts
|

Induced pluripotent stem cells established from a female patient with Xq22 deletion confirm that BEX2 escapes from X‐chromosome inactivation

Abstract: Large deletions in Xq22 are responsible for neurodevelopmental disorders, including severe intellectual disability and behavioral abnormalities. Although the deletion regions contain PLP1, the gene related to Pelizaeus‐Merzbacher disease (PMD), patients with Xq22 deletions show no clinical features of PMD such as paraplegia and white matter abnormalities. This could be due to skewed X‐chromosome inactivation (XCI) occurring predominantly in the affected allele. Isogenic pairs of wild type and mutant induced pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Given that this gene is down-regulated in a variety of viral infections, it may be that Bex2 is a protective gene that is targeted for inhibition by the invading virus. A recent study in induced pluripotent stem cells has shown that Bex2 is capable of escaping X-chromosome inactivation (Yamamoto-Shimojima et al, 2021), thereby giving females potentially two functional copies. It should also be noted that Bex1 and 2 was found to be colocalized with the olfactory marker protein (OMP) in mature olfactory receptor neurons (Koo et al, 2005), suggesting a mechanism for loss of smell in the host after viral infection.…”
Section: Bex2 In Host Response To Coronavirus Infectionmentioning
confidence: 99%
“…Given that this gene is down-regulated in a variety of viral infections, it may be that Bex2 is a protective gene that is targeted for inhibition by the invading virus. A recent study in induced pluripotent stem cells has shown that Bex2 is capable of escaping X-chromosome inactivation (Yamamoto-Shimojima et al, 2021), thereby giving females potentially two functional copies. It should also be noted that Bex1 and 2 was found to be colocalized with the olfactory marker protein (OMP) in mature olfactory receptor neurons (Koo et al, 2005), suggesting a mechanism for loss of smell in the host after viral infection.…”
Section: Bex2 In Host Response To Coronavirus Infectionmentioning
confidence: 99%